2008
DOI: 10.1021/jp802001g
|View full text |Cite
|
Sign up to set email alerts
|

Calculated Band Profiles of the OH-Stretching Transitions in Water Dimer

Abstract: We have calculated the band profiles of the OH-stretching fundamental and overtone transitions in the proton donor unit of the water dimer complex. We have used a local mode Hamiltonian that includes both OH-stretching and OO-stretching motion but separates these adiabatically. The variation of OH-stretching frequency and anharmonicity with OO displacement from equilibrium contributes to the effective OO-stretching potentials for each OH-stretching state. The resulting OO-stretching energy levels and wave func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…Nevertheless, analysis of the temperature dependence of the residual absorption cross-section allowed a clear distinction between the contribution of water dimers (which has a strong negative T-dependence) and the cumulative local contribution from water monomer lines (which is nearly independent of temperature). Our own work (Ptashnik et al 2004;Paynter et al 2007) indicated wellpronounced absorption spectral features that are in a reasonable agreement, in both strength and position, with those expected from the calculated dimer spectra (Schofield and Kjaergaard 2003;Garden et al 2008). Ptashnik (2008) reviews the evidence that similar spectral features could also be seen in earlier measurements of, for example, Burch (1985), Vetrov andYukhnevich (1975), andPoberovsky (1976).…”
Section: Post-2000supporting
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, analysis of the temperature dependence of the residual absorption cross-section allowed a clear distinction between the contribution of water dimers (which has a strong negative T-dependence) and the cumulative local contribution from water monomer lines (which is nearly independent of temperature). Our own work (Ptashnik et al 2004;Paynter et al 2007) indicated wellpronounced absorption spectral features that are in a reasonable agreement, in both strength and position, with those expected from the calculated dimer spectra (Schofield and Kjaergaard 2003;Garden et al 2008). Ptashnik (2008) reviews the evidence that similar spectral features could also be seen in earlier measurements of, for example, Burch (1985), Vetrov andYukhnevich (1975), andPoberovsky (1976).…”
Section: Post-2000supporting
confidence: 77%
“…Interest in the role of water dimers in the atmospheric science literature was reinvigorated by Vaida et al (2001), and in a subsequent series of papers by co-authors (e.g., Schofield and Kjaergaard 2003;Kjaergaard et al 2008;Garden et al 2008) focusing on the near-infrared region. These papers applied quantum chemistry methods to perform ab initio calculations of both the potential energy surface and the dipole moment function for the water dimer, in order to then produce computations of the strengths and positions of the vibrational bands of the water dimer.…”
Section: Post-2000mentioning
confidence: 99%
“…Indeed, the results of the calculations in Table I show that FD is predominantly a parallel band, which is also in agreement with other recent calculations. 42 Apparently, the vibration of the bond bridge H-atom gives a large contribution to the transition dipole in spite of its relatively small amplitude. Some weak splitting of the FD band of about 1 cm −1 as shown in the insert to Fig.…”
Section: The Free Donor Oh-stretch Band "Fd…mentioning
confidence: 99%
“…8,[25][26][27][28][29][30][31] Water dimers continue to be a target of extensive quantum chemical calculations. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Calculated equilibrium structure of water dimer is shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, adiabatic separation methods that have been applied for some smaller polyatomic clusters exist [7][8][9][10]. In particular, methods such as MULTIMODE by Bowman et al [11][12][13] and the harmonically coupled anharmonic oscillator methods by Kjaergarrd et al [8,[14][15][16][17][18] have been used to describe vibrationrotation-tunnelling (VRT) states in small polyatomic clusters including the water dimer. These methods decouple the modes to make the calculations tractable.…”
Section: Introductionmentioning
confidence: 99%